Chemoinformatics and artificial intelligence colloquium: progress and challenges in developing bioactive compounds - Bajorath, Jürgen; Chávez-Hernández, Ana L.; Duran-Frigola, Miquel; Fernández-de Gortari, Eli; Gasteiger, Johann; López-López, Edgar; Maggiora, Gerald M.; Medina-Franco, José L.; Méndez-Lucio, Oscar; Mestres, Jordi; Miranda-Quintana, Ramón Alain; Oprea, Tudor I.; et al. (Journal of cheminformatics, 2022)
We report the main conclusions of the first Chemoinformatics and Artificial Intelligence Colloquium, Mexico City, June 15–17, 2022. Fifteen lectures were presented during a virtual public event with speakers from industry, academia, and non-for-profit organizations. Twelve hundred and ninety students and academics from more than 60 countries. During the meeting, applications, challenges, and opportunities in drug discovery, de novo drug design, ADME-Tox (absorption, distribution, metabolism, excretion and toxicity) property predictions, organic chemistry, peptides, and antibiotic resistance were discussed. The program along with the recordings of all sessions are freely available at https://www.difacquim.com/english/events/2022-colloquium/ .